WEIGHTED STATISTICAL CONVERGENCE OF ORDER ? IN PARANORMED SPACES - Çınar, Muhammed; Et, Mikail; Karakaş, Murat (My University, 2020)
In this study, we introduce and examine the concept of weighted statisticalconvergence of order ? in paranormed spaces. Also some relations between weightedstatistical convergence of order ? and N, pn, g?r?summability are given